Propuesta para la impartición de cursos cortos sobre internet de las cosas a niños de Educación Básica - Doicela Ayala, William Ramon (2024)
The research project proposes an educational methodology that integrates the Internet of Things (IoT) into the curriculum of basic education children. The STEAM (Science, Technology, Engineering, Art and Mathematics) approach is applied to develop critical and creative skills in students, preparing them for the challenges of the technological future. A short course was designed that not only introduces children to fundamental IoT concepts, but also uses up-to-date hardware and software tools to facilitate interactive and hands-on learning. The implementation of the course includes several stages: from the organization of the necessary tools to the evaluation of the usability and effectiveness of the course through satisfaction questionnaires and the System Usability Scale (SUS). Preliminary results indicate that students improved significantly in their understanding and applicability of the IoT, reflecting the success of the pedagogical approach adopted. The research highlights the importance of continually adapting educational materials and pedagogical strategies to maintain course relevance and effectiveness. Implementation of a continuous feedback system is recommended to collect student feedback and make necessary adjustments. This approach not only enhances the learning experience, but also ensures that IoT education remains aligned with the changing needs of society and technology.